Rotational Lopping of Eucalyptus in the Nilgiris - Chaturvedi, M. D. (Indian Forester, 1951)
Experience gained in the Saharanpur Siwaliks and nearer home in the Nilgiris themselves in the privately owned estates, suggests the adoption of rotational lopping of the State plantations of Eucalyptus to support the cottage industry producing Eucalyptus oil. Retention of 1/5th of the crown at the top at the time of lopping and a rest of full 4 growing seasons after each lop is to be rigidly enforced. In addition to making India self-sufficient in respect of Eucalyptus oil, the scheme will yield an additional annual income of Rs. 50,000 and provide means of livelihood to the local population during the winter season when it has little to do.